Vague soft hypermodules; connections with soft hypermodules and homomorphisms - Tahere Nozari; Morteza Norouzi (Journal of Hyperstructures)
In this paper, the notion of vague soft hypermodules is introduced, which is an extension of the notions of vague soft hypergroups and vague soft hyperrings. Also, some basic properties of vague soft hypermodules and homomorphisms between vague soft hypermodules are presented and the image and pre-image of a vague soft hypermodule under a vague soft hypermodule homomorphism are studied.